Simplify.


(
6
x
3
y
)
(
2
x
y
2
)
(6x
3
y)(2xy
2
) Hint: Multiply the 6 and 2...then use the exponent rules for the variables.

1 answer

To simplify the expression \((6x^3y)(2xy^2)\), follow these steps:

  1. Multiply the coefficients: \(6\) and \(2\). \[ 6 \times 2 = 12 \]

  2. Multiply the variable \(x\): \[ x^3 \text{ (from the first term)} \cdot x \text{ (from the second term)} = x^{3+1} = x^4 \]

  3. Multiply the variable \(y\): \[ y \text{ (from the first term)} \cdot y^2 \text{ (from the second term)} = y^{1+2} = y^3 \]

Now, combine all parts together: \[ 12x^4y^3 \]

So, the simplified expression is: \[ \boxed{12x^4y^3} \]

Similar Questions
  1. simplifying square roots1) find volume of this prism? v=bwh b=√12" w=√6" h=√8" 2)simplify: √576 3)simplify: √400
    1. answers icon 3 answers
  2. Simplify 8a − 2a.Simplify 12e − 5f − 7e +3f. Simplify 9x + 3y − 6 − 5x + 4y −3. Simplify 9/11z − 4/11z. Simplify
    1. answers icon 4 answers
  3. simplifying square roots1) find volume of this prism? v=bwh b=√12" w=√6" h=√8" 2)simplify: √576 3)simplify: √400
    1. answers icon 3 answers
  4. So I need some help on these Graphing Square Root Functions Quiz questions.1. Simplify 2 over √5 2. Simplify -11√112 3.
    1. answers icon 1 answer
more similar questions